246 Peyronie's Disease - Outcomes of Collagenase Clostridium Histolyticum Injection: A Systematic Review. (1st May 2022) - Mefford, A; Alzweri, L; Raheem, O; Yafi, F
ABSTRACT: Introduction: Peyronie's Disease (PD) is a condition characterized by abnormal and excessive wound repair causing fibrous plaquing of the tunica albuginea. Intralesional (IL) therapies are for patients who prefer to avoid surgical intervention and associated adverse complications. Currently, among available IL injection therapies (Collagenase Clostridium histolyticum (CCh) (Xiaflex, Endo Pharmaceuticals, Dublin, Ireland), verapamil, IFN-a-2b, OnabotulinumtoxinA (Botox) (AbbVie, Chicago, Illinois), Hyaluronic acid). The only FDA approved intralesional treatment option is CCh, which recently expanded its indications for atypical PD. Objective: This study aims to review recent literature pertaining to CCh and other intralesional therapies in treatment of PD. Methods: A systematic search of literature using exclusively PubMed was performed. There were no specific inclusion or exclusion criteria, however a preference was placed on recent and high impact articles. The review represents many types of studies including randomized control trials, meta-analyses, as well as phase 2 and 3 clinical trials. The use of CCh was compared to other IL therapies and evaluated for efficacy. This included Lastly, CCh use in atypical Peyronie's Disease was assessed for rate of success and complication. Results: Recent literature supports the notion that CCh is the most superior IL treatment for typical and atypical PD patients. The capstone CCh study was the IMPRESS trial that showed a 34% reduction in curvature with a mean -17.0 ± 14.8 angle reduction with IL CCh, while men in the placebo saw an average 18.2% decrease in penile bend with a mean -9.3 ± 13.6 degree of change per person (p<0.0001). A shortened protocol for IL CCh treatment offered a 31.4% reduction in curvature while decreasing cost and office visits, potentially increasing patient compliance. Lastly, the literature shows CCh is used most commonly in atypical cases with about 64.8% of patients being treated with CCh – this is probably because of the high efficacy and superb safety profile that it offers. The most serious complications associated with CCh including urethral injury, corporal rupture and penile fracture are rare in all types of PD. Conclusion: Since the approval of CCh by the FDA in 2013, it has been a staple in the treatment of PD, and here we report the continued success and superiority of this therapy. CCh is an effective, minimally invasive therapeutic option in most PD populations, however recent changes have made CCh unavailable for commercial use out of the United States, thus impacting many patients who have previous benefited from it. Disclosure: Work supported by industry: no.